Eye Tracking in Driver Attention Research—How Gaze Data Interpretations Influence What We Learn - Ahlström, Christer; Kircher, Katja; Nyström, Marcus; Wolfe, Benjamin (Frontiers in Neuroergonomics, 2021)
Eye tracking has been used extensively in driver attention research. Amongst other findings, eye tracking data have increased our knowledge about what drivers look at in different traffic environments and how they distribute their glances when interacting with non-driving related tasks. Eye tracking is also the go-to method when determining driver distraction via glance target classification. At the same time, eye trackers are limited in the sense that they can only objectively measure the gaze direction. To learn more about why drivers look where they do, what information they acquire foveally and peripherally, how the road environment and traffic situation affect their behaviour, and how their own expertise influences their actions, it is necessary to go beyond counting the targets that the driver foveates. In this perspective paper, we suggest a glance analysis approach that classifies glances based on their purpose. The main idea is to consider not only the intention behind each glance, but to also account for what is relevant in the surrounding scene, regardless of whether the driver has looked there or not. In essence, the old approaches, unaware as they are of the larger context or motivation behind eye movements, have taken us as far as they can. We propose this more integrative approach to gain a better understanding of the complexity of drivers’ informational needs and how they satisfy them in the moment.